Study of Some Histological and Biochemical Changes in Patients with Celiac Disease - Ilham Abd Allah Ali Al-Saleem (Journal of Global Pharma Technology, 2018)
Introduction: Celiac disease (CD), a common heritable chronic inflammatory condition in the small intestine caused by permanent intolerance to gluten/gliadin. Aim of object: to investigate the disorders associated CD. Materials and methods: The present study carried out on the 30 patient’s and25 individuals as control group had been clinically diagnosed as celiac who underwent endoscopic examinations due to gastrointestinal symptoms. Blood samples were collected from the groups for determination of serum transaminase enzyme. The patients underwent upper gastrointestinal endoscopy. Three biopsies were taken from the second portion of the duodenum, fixed in 10% formalin embedded in paraffin. Marsh scores used for the histological evaluation of the intestinal mucosa damage that have been suggested .Results: This study demonstrated that 25(45.5%) in the total of 30(54.5%) of patients with celiac disease at the age under than 12 years old associated with Glutamic- pyruvic transaminase higher level. This study also demonstrated that 22(40.0%) from a total 27 of patients with celiac disease are associated with Glutamic- Oxaloacetic Transaminase higher level are under 12 years. From our results we found that 8(14.5%)of a type 3a and18(32.7%) of a type 3b,when we retain to the marsh classification .In the sections of duodenal mucosa in study group. we show increase intra epithelial lymphocytes and also the sections revealed crypt hyperplasia, focal partial villous atrophy and subtotal villous atrophy .Conclusions: this study demonstrated that there is a positive relationship between CD and hypertansaminase and the majority of them are of type3 of marsh classification.  Key words:  Biopsy-celiac disease scores- crypt hyperplasia- hypertransaminase- intraepithelial lymphocyte- mucosa damage- villous atrophy.